2022
DOI: 10.1111/evo.14411
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of sexual selection affects microRNA profiles in Drosophila sperm

Abstract: The presence of small RNAs in sperm is a relatively recent discovery and little is currently known about their importance and functions. Environmental changes including social conditions and dietary manipulations are known to affect the composition and expression of some small RNAs in sperm and may elicit a physiological stress response resulting in an associated change in gamete miRNA profiles. Here, we tested how microRNA profiles in sperm are affected by variation in both sexual selection and dietary regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In Drosophila for example, miRNA profiles in sperm collected from males from long-term selection lines exposed to varying sex ratios (equal sex ratio, male bias, or female bias for 38 generations) varied by 11 differentially expressed miRNA [13]. Notably, miR-9b-5pan miRNA that is enriched in male primordial germ cells onlywas reduced in the sperm from males sampled from female-biased lines compared to males from male-biased lines [14]. Whether these differentially expressed miRNAs affect the following generations is currently unclear and warrants further study.…”
Section: Mirnas and Germ Cell Development In Changing Environmentsmentioning
confidence: 99%
“…In Drosophila for example, miRNA profiles in sperm collected from males from long-term selection lines exposed to varying sex ratios (equal sex ratio, male bias, or female bias for 38 generations) varied by 11 differentially expressed miRNA [13]. Notably, miR-9b-5pan miRNA that is enriched in male primordial germ cells onlywas reduced in the sperm from males sampled from female-biased lines compared to males from male-biased lines [14]. Whether these differentially expressed miRNAs affect the following generations is currently unclear and warrants further study.…”
Section: Mirnas and Germ Cell Development In Changing Environmentsmentioning
confidence: 99%
“…Ejaculate [110], [111], [112] Ejaculate [113] Milk [30] Saliva [111] Eggs [99] Regurgitate [90] Nucleotides Ejaculate [97] Ejaculate [97] Milk [26] Proteins Ejaculate [103], [114] e.g. immunoregulatory factors, cytokines FRF [115] Ejaculate [116],…”
Section: Rnamentioning
confidence: 99%
“…In D . melanogaster it has been shown that long-term adaptation may affect miRNA profiles in sperm and that these may show varied interactions with short-term environmental changes [ 16 ]. Organisms appear to protect certain RNAs by design.…”
Section: Introductionmentioning
confidence: 99%
“…Additonally, piRNA cluster causes the complex changes in stresscoping behaviors, metabolism and stress-induced glucose release in the offspring [6,14]. In D. melanogaster it has been shown that long-term adaptation may affect miRNA profiles in sperm and that these may show varied interactions with short-term environmental changes [16]. Organisms appear to protect certain RNAs by design.…”
Section: Introductionmentioning
confidence: 99%